2002
DOI: 10.1111/j.1460-2466.2002.tb02573.x
|View full text |Cite
|
Sign up to set email alerts
|

Black and White Viewers' Perception and Recall of Occupational Characters on Television

Abstract: This study examined the differences in how Black and White viewers process messages based on the race of television characters representing 5 occupations. Black and White male viewers were exposed to either 5 Black or 5 White male television characters representing 5 different occupations (i.e., lawyer, doctor, professor, engineer, and business student). Findings from 81 male Black and White college students suggest that Black viewers have better recall of Black occupational characters on television than they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 40 publications
(53 reference statements)
4
48
0
Order By: Relevance
“…These results suggest that negative stereotypes are more susceptible to information and media influence. This supports previous research that has shown negative information can be more influential than positive information (e.g., Fiske, 1980), and the media can form and reinforce negative stereotypes of African-Americans (e.g., Appiah, 2002;Dixon, 2006;Oliver, 1999;Rada, 2000). Taking this into consideration, and because prior studies revealed that negative stereotypes of African-Americans may influence opinions on race-coded issues (Mastro & Kopacz, 2007;Tan et al, 2000) and prime racial attitudes during evaluations of a U.S. president (Valentino, 1999), future studies might consider investigating whether foreign residents' stereotypes, and their exposure to negative portrayals of African-Americans could influence their opinions of the foreign policies of President Barrack Obama (the first AfricanAmerican president of the United States) and his administration.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results suggest that negative stereotypes are more susceptible to information and media influence. This supports previous research that has shown negative information can be more influential than positive information (e.g., Fiske, 1980), and the media can form and reinforce negative stereotypes of African-Americans (e.g., Appiah, 2002;Dixon, 2006;Oliver, 1999;Rada, 2000). Taking this into consideration, and because prior studies revealed that negative stereotypes of African-Americans may influence opinions on race-coded issues (Mastro & Kopacz, 2007;Tan et al, 2000) and prime racial attitudes during evaluations of a U.S. president (Valentino, 1999), future studies might consider investigating whether foreign residents' stereotypes, and their exposure to negative portrayals of African-Americans could influence their opinions of the foreign policies of President Barrack Obama (the first AfricanAmerican president of the United States) and his administration.…”
Section: Discussionsupporting
confidence: 82%
“…When opportunities for direct contact are lacking, the media serve as important agents in the formation of stereotypes (e.g., Appiah, 2002;Dixon, 2006;Fujioka, 1999;Oliver, 1999;Rada, 2000). Cultivation theory suggests that there is a direct correlation between the media's portrayals of social groups and audiences' perceptions (Gerbner et al, 2002).…”
Section: Stereotypes Media and Informationmentioning
confidence: 98%
See 1 more Smart Citation
“…Sympathy Towards the Suspect was measured using 3 items adapted from Batson, Fultz, and Schoenrade (1987) Attitude Towards the Suspect and Attitude Towards the Victim were measured using 11 semantic differential items as modeled in Appiah (2002), Devine and Elliot (1995), and Peffley, Hurwitz and Sniderman (1997). The following pairs were used: lazy/hardworking, unreliable/dependable, undisciplined/disciplined, violent/peaceful, unintelligent/intelligent, poor/rich, immoral/moral, unsuccessful/successful, untidy/neat, naïve/sophisticated, criminal/law-abiding (Attitude Towards Suspect: M = 3.75, SD = 1.11, α = 0.93; Attitude Towards Victim: M = 3.29, SD = 1.10, α = 0.94).…”
Section: Methodsmentioning
confidence: 99%
“…Group identity is especially salient for members of minority groups, and studies show that they prefer content featuring members of their minority in-groups in the media (Appiah, 2001(Appiah, , 2002Fujioka, 2005). Audience members from minority groups are conscious of features that might mark them as distinct from the majority group and are particularly sensitive to how they are represented in popular media, in which they are often typically invisible.…”
Section: Social Identity and Social Cognitive Theorymentioning
confidence: 97%